Analisis Kebijakan Pemerintah Daerah dalam Penanggulangan Kemiskinan di Kabupaten Maros - Febryanty Fajry (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This study aims to determine and to analyze the effort of local government to overcome poverty in Maros regency and factors that influence it. To achieve the objectives the researcher using a method of qualitative research and exploring data descriptively. The data collecting technique was done through observation, in-depth interview, document and archieveby using qualitative analysis technique. The result study shows two things: first, the effort of local government to overcome poverty that conducted by Department of Social, Labor and Transmigration and Department of Cooperation, Industrial and Trading of Marod regency through the poverty overcoming program includes Expectancy Family Program (PKH), the Poor Empowerment Program (KUBE-FM) and Micro, Small, Medium-Sized Enterprise Empowerment Program. Second, in its implementation there are several factor that influence it, consist of supporting and inhibiting factor. The supporting factor is the presence of commitment between state and local government, good coordination inter actor who involved, the cooperation between related parties, the motivation of each members to participate in each activities, integrated organization structure and technological utilization. And the inhibiting factors is the lack of poor understanding about sanction if violate the obligation, restricted budget, the lack of human resources quality, the lack of relationship for each member, the lack of ability that owned by bussines actor and inadequate means and infrastructure.